Object Detection and Filtering Techniques of Underwater Images : A Review - Martin, Martina; Mishra, Nishchol (International Journal of Computer Sciences and Engineering, 2019)
As going deep under the water nothing can be seen properly as well as it is difficult to identify any substance residing or present under water. This survey basically focuses on the detection of the underwater image which are taken through various self-ruling submerged vehicles and remotely controlled vehicles, in order to improve the quality of the pictures. The factors include the low contrast, blur, non-uniform lighting and faded colors. This paper analyzed an image enhancement technique alon.